Dynamic interactions in the tumor niche: how the cross-talk between CAFs and the tumor microenvironment impacts resistance to therapy - Piwocka, Oliwia; Piotrowski, Igor; Suchorska, Wiktoria M.; Kulcenty, Katarzyna (Frontiers in Molecular Biosciences, 2024)
The tumor microenvironment (TME) is a complex ecosystem of cells, signaling molecules, and extracellular matrix components that profoundly influence cancer progression. Among the key players in the TME, cancer-associated fibroblasts (CAFs) have gained increasing attention for their diverse and influential roles. CAFs are activated fibroblasts found abundantly within the TME of various cancer types. CAFs contribute significantly to tumor progression by promoting angiogenesis, remodeling the extracellular matrix, and modulating immune cell infiltration. In order to influence the microenvironment, CAFs engage in cross-talk with immune cells, cancer cells, and other stromal components through paracrine signaling and direct cell-cell interactions. This cross-talk can result in immunosuppression, tumor cell proliferation, and epithelial-mesenchymal transition, contributing to disease progression. Emerging evidence suggests that CAFs play a crucial role in therapy resistance, including resistance to chemotherapy and radiotherapy. CAFs can modulate the tumor response to treatment by secreting factors that promote drug efflux, enhance DNA repair mechanisms, and suppress apoptosis pathways. This paper aims to understand the multifaceted functions of CAFs within the TME, discusses cross-talk between CAFs with other TME cells, and sheds light on the contibution of CAFs to therapy resistance. Targeting CAFs or disrupting their cross-talk with other cells holds promise for overcoming drug resistance and improving the treatment efficacy of various cancer types.